(untitled) (Journal of Pathology of Nepal, 2014)
Background: Approximately 10% of breast masses are breast cancer. It is important for women with a breast lump to receive appropriate evaluation. Mammography has been the “gold standard” in breast cancer detection for >40 years. Ultrasonography is non-invasive easily available, cheaper and accurate tool while Fine needle aspiration cytology has a high diagnostic accuracy rate in hands of experienced cytopathologist. Materials and methods: This was a retrospective and prospective study of 173 women attending radiology department in Manipal Teaching Hospital, Pokhara for mammography during a period of 18 months from January 2011 to June 2012.The age ranged from 20yrs to 75yrs. BIRADS score was given for both mammography and sonomammography. All malignant and suspicious cases had undergone fine needle aspiration cytology. Cytology reports were correlated with imaging study. Results: The most common age group for the breast lump was 40-49 years showing 65(37.57%) cases. Most lumps were seen on the left side 54.3% (94/ 173) cases and were seen in upper outer quadrant of the breast (74 cases). 11 cases each were given the BIRADS score of 4 in both mammography and sonomammography. Sensitivity and specificity of mammography and sonomammography were compared to cytologyreports. The sensitivity for mammogram was 73.7% while specificity was 96.3%. The sensitivity and specificity for sonomammogram was 78.9% and 95% respectively. Conclusion: Quadruple assessment i.e. clinical assessment, mammography, sonomammography and cytological study are the new “gold standard” in the investigation of breast disease. DOI: http://dx.doi.org/10.3126/jpn.v4i8.11499 Journal of Pathology of Nepal; Vol.4,No. 8 (2014) 630-634